Penentuan Kinerja Organisasi Pemerintah Daerah di Kabupaten Musi Banyuasin, Provinsi Sumatera Selatan - Indra S; Sulaiman Sulaiman; Chandra Satria; M Thoyib; Ade L; Adit A (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2019)
This study aims to determine and analyze the influence of Determination of Organizational Performance of Regional Devices of the Government of Musi Banyuasin Regency in South Sumatra Province The data in this study were collected using the method of observation and survey through interviews and with the help of research instruments in the form of questionnaires totaling 144 examinations which were distributed directly to 52 local government organizations in Musi Banyuasin Regency, which were addressed directly to regional heads. work units, secretaries and section heads who work for local government organizations. Data in this study will be analyzed using multiple linear regression with the help of SPSS software version 24.0. To test the validity and reliability of research instruments used the Correlation Item-Total Correction and Cronvach's Alpha. In addition, data normalization is also tested using the normal probability plot. The results of this study indicate that of these four variables; Clarity of budget targets, internal control systems, good governance, and professionalism have a positive and significant effect on organizational performance either partially or simultaneously.